2017
DOI: 10.1186/s12906-016-1514-1
|View full text |Cite
|
Sign up to set email alerts
|

Kudiezi injection mitigates myocardial injury induced by acute cerebral ischemia in rats

Abstract: BackgroundKudiezi (KDZ) injection is commonly used in traditional Chinese medicine as treatment for cerebral infarction and angina pectoris. The present study investigated the therapeutic effects of KDZ injection on myocardial injury induced by acute cerebral ischemia and the possibly protective mechanisms.MethodsRats were divided into three groups: sham, 6h-ischemia, and KDZ treatment (KDZ). The neurological deficits were determined by the Garcia score. The cerebral infarct volume was measured by 2,3,5-triphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Sun and Yang found that metformin improved the myocardial function of mice with heart failure following MI according to regulation of the expression of SIRT3 and PGC-1α in the mitochondrial inner membrane (58). However, mitochondrial dysfunction is not unique to MI; energy metabolism barriers can also occur in acute cerebral ischemia (59), renal ischemia (60), liver ischemia (61) and other ischemic diseases. This provides a novel direction in order to understand the process of MI, and further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…Sun and Yang found that metformin improved the myocardial function of mice with heart failure following MI according to regulation of the expression of SIRT3 and PGC-1α in the mitochondrial inner membrane (58). However, mitochondrial dysfunction is not unique to MI; energy metabolism barriers can also occur in acute cerebral ischemia (59), renal ischemia (60), liver ischemia (61) and other ischemic diseases. This provides a novel direction in order to understand the process of MI, and further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…Only levels of various serum inflammatory factors were measured, and other pathological processes involved in ischemic damage (e.g., oxidative stress) were not assessed. A previous study in rats showed that Kudiezi injection could decrease oxidative stress after stroke, as well as secondary myocardial damage in rats [ 25 ]. This aspect could be worth exploring in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the balance between oxidative stress and antioxidant capacity is involved in the extent of damage after ischemic stroke [ 24 ]. Kudiezi injection has been shown to shift the balance toward decreased oxidative stress in rats [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some herbal medicine injections produced by extracting and purifying active ingredients from herbs or decoctions according to modern scienti c and technological theories have often been used to treat some emergency and severe diseases in clinics in China. Kudiezi (KDZ) injection, a typical representative of herbal medicine injections, is extracted from the herb Ixeris denticulate and extensively applied to treat ischemic stroke and myocardial infarction [12]. Studies have shown that KDZ injection mainly contains avonoids, adenosine, sesquiterpene lactones and triterpene saponins [13].…”
Section: Introductionmentioning
confidence: 99%